Adsorption and self-assembly properties of the plant based biosurfactant, Glycyrrhizic acid - Tucker, IM; Burley, A; Petkova, RE; Hosking, SL; Penfold, J; Thomas, RK; Li, PX; Webster, JRP; Welbourn, R; Doutch, J (Elsevier, 2021)
There is an increased interest in the use of natural surfactant as replacements for synthetic surfactants due to their biosustainable and biocompatible properties. A category of natural surfactants which are attracting much current interest is the triterpenoid saponins; surface active components found extensively in a wide range of plant species. A wide range of different saponin structures exist, depending upon the plant species they are extracted from; but regardless of the variation in structural details they are all highly surface active glycosides. Greater exploitation and application requires a characterisation and understanding of their basic adsorption and self-assembly properties. Hypothesis Glycyrrhizic acid, extracted from Licorice root, is a monodesmosidic triterpenoid saponin. It is widely used in cosmetic and pharmaceutical applications due to its anti-inflammatory properties, and is an ingredient in foods as a sweetener additive. It has an additional attraction due to its gel forming properties at relatively low concentrations. Although it has attracted much recent attention, many of its basic surface active characteristics, adsorption and self-assembly, remain relatively unexplored. How the structure of the Glycyrrhizic acid saponin affects its surface active properties and the impact of gelation on these properties are important considerations, and to investigate these are the focus of the study. Experiments In this paper the adsorption properties at the air-water interface and the self-assembly in solution have been investigated using by neutron reflectivity and small angle neutron scattering; in non-gelling and gelling conditions. Findings The adsorption isotherm is determined in water and in the presence of gelling additives, and compared with the adsorption behaviour of other saponins. Gelation has minimal impact on the adsorption; apart from producing a rougher surface with a surface texture on a macroscopic length scale. Globular micelles are formed in aqueous solution with modest anisotropy, and are compared with the structure of other saponin micelles. The addition of gelling agents results in only minimal micelle growth, and the solutions remain isotropic under applied shear flow.